Effect of coital activity on onset of labor in women scheduled for labor induction - A randomized controlled trial - Tan, P.C.; Yow, C.M.; Omar, S.Z. (2007)
OBJECTIVE: To estimate the effect of coitus on the onset of labor. METHODS: Women with a nonurgent labor induction at term were recruited. Women randomly assigned to the advised-coitus group were encouraged to have sex to promote the onset of labor. Controls were neither encouraged nor discouraged regarding coitus. Participants kept a coital and orgasm diary until delivery, and standard obstetric care was provided to both groups. Primary outcomes were reported coitus and spontaneous labor. Secondary outcomes included reported orgasms, initial Bishop score at the admission for induction, preterm rupture of membranes, use of dinoprostone, oxytocin, or epidural, meconium-stained amniotic fluid, cesarean delivery, maternal fever, and neonatal morbidity. RESULTS: One hundred eight and 102 women randomly assigned to advised-coitus and control groups, respectively, were available for analysis. Women assigned to the advised-coitus group were more likely to report coital activity before delivery (60.2 compared with 39.6, relative risk 1.5, 95 confidence interval 1.1-2.0; P=.004), but the spontaneous labor rate was no different (55.6 compared with 52.0, relative risk 1.1, 95 confidence interval 0.8-1.4; P=.68). Cesarean delivery rate and neonatal and other secondary outcomes were also not different. CONCLUSION: Among women scheduled for labor induction who were advised to have sex, the increase in sexual activity did not increase the rate of spontaneous labor. CLINICAL TRIAL REGISTRATION: isrctn.org, http://isrctn. org, ISRCTN17998696.